Synthesis and biological evaluation of polysulfated oligosaccharide glycosides as inhibitors of angiogenesis and tumor growth - Johnstone, Ken D.; Karoli, Tomislav; Liu, Ligong; Dredge, Keith; Copeman, Elizabeth; Li, Cai Ping; Davis, Kat; Hammond, Edward; Bytheway, Ian; Kostewicz, Edmund; Chiu, Francis C. K.; Shackleford, David M.; et al. (Journal of medicinal chemistry, 2010)
A series of polysulfated penta- and tetrasaccharide glycosides containing α(1→3)/α(1→2)-linked mannose residues were synthesized as heparan sulfate (HS) mimetics and evaluated for their ability to inhibit angiogenesis. The compounds bound tightly to angiogenic growth factors (FGF-1, FGF-2, and VEGF) and strongly inhibited heparanase activity. In addition, the compounds exhibited potent activity in cell-based and ex vivo assays indicative of angiogenesis, with tetrasaccharides exhibiting activity comparable to that of pentasaccharides. Selected compounds also showed good antitumor activity in vivo in a mouse melanoma (solid tumor) model resistant to the phase III HS mimetic 1 (muparfostat, formerly known as PI-88). The lipophilic modifications also resulted in reduced anticoagulant activity, a common side effect of HS mimetics, and conferred a reasonable pharmacokinetic profile in the rat, as exemplified by the sulfated octyl tetrasaccharide 5. The data support the further investigation of this class of compounds as potential antiangiogenic, anticancer therapeutics.